A comparative clinical picture of dementia (One Health & Risk Management, 2021)
Introduction. The prevalence of dementia is increasing in our population, which is aging at an alarm-ing rate. Due to the heterogeneity of the clinical presentation and the complexity of the neuropathology of the disease, the classifications of dementia remain controversial, and the number of people diagnosed does not correspond, even remotely, with reality. About 47 million people live with dementia globally; by 2050, there will be an almost threefold increase to about 131 million people with dementia. Also, the costs for the diagnosis, treatment and post-treatment surveillance of dementia for the health system and the economy are significant. The clinical picture of dementia is quite diverse. Therefore, it is necessary to learn how to relate its different symptoms and syndromes, characteristics and specificity in different nosologies.Material and methods. The present work studied 42 materials and literature sources from the Medscape, PubMed and EBSCO databases in terms of clinical manifestations, symptoms and syndromes of dementia (2013-2021). Most of the used literature sources refer to the last years of publication (2016-2021). The methods of study were as follows: 1. The clinical-descriptive method of the main symptoms, syndromes, 2. The comparative-clinical analysis of the symptoms of dementia, 3. The specific clinical features, 4. The differential diagnosis between different types of dementia, 5. The 4 most common dementia types, 6. Dementia in different nosologies, 7. The most common conditions viz. depression and delirium, should be differentiated from dementia in the first place. Major attention was paid to the comparative characteristics and clinical manifestations of different types of dementia in various pathologies, to the point of specific features of dementia. A comparative clinical picture of deep cognitive changes and development was studied according to the REIBERG scale for dementia. There were applied current classifications of dementia: DSM-V, ICD-X, ICD-11. The scientific novelty of the work is provided by the use of ICD-11 in the description of the criteria for the diagnosis of dementia.Results. The paper lists the risk factors, protection factors and pathogenesis of dementia. The study results provided a generalization of specific symptoms and syndromes in the most common 4 types of dementia: 1. Dementia in Alzheimer’s Disease, 2. Lewy Body Dementia, 3. Vascular Dementia, 4. Frontotemporal Dementia, as well as dementia occurring in other nosologies. Comparative differential criteria for the diagnosis of dementia and other underlying conditions which are difficult to differentiate from dementia viz. depression and delirium were also studied.Conclusions. Failure to recognize dementia syndromes remains common. Different types of dementia require different approaches and management. From a long list of differential diagnoses of dementia, four common types should come to mind (Alzheimer's disease, vascular dementia, Lewy body dementia and frontotemporal dementia) just by taking patient’s family history, physical examination and checking the patient’s behavioral status. Dementia should be differentiated from the most common conditions like depression and delirium by nosology, clinical presentation, prevailing symptoms and syndromes.